Molecular diagnostics for lassa fever at Irrua specialist teaching hospital, Nigeria: lessons learnt from two years of laboratory operation. - Danny A Asogun; Donatus I Adomeh; Jacqueline Ehimuan; Ikponmwonsa Odia; Meike Hass; Martin Gabriel; Stephan Olschläger; Beate Becker-Ziaja; Onikepe Folarin; Eric Phelan; Philomena E Ehiane; Veritas E Ifeh; et al. (Public Library of Science (PLoS), 2012)
BACKGROUND: Lassa fever is a viral hemorrhagic fever endemic in West Africa. However, none of the hospitals in the endemic areas of Nigeria has the capacity to perform Lassa virus diagnostics. Case identification and management solely relies on non-specific clinical criteria. The Irrua Specialist Teaching Hospital (ISTH) in the central senatorial district of Edo State struggled with this challenge for many years. METHODOLOGY/PRINCIPAL FINDINGS: A laboratory for molecular diagnosis of Lassa fever, complying with basic standards of diagnostic PCR facilities, was established at ISTH in 2008. During 2009 through 2010, samples of 1,650 suspected cases were processed, of which 198 (12%) tested positive by Lassa virus RT-PCR. No remarkable demographic differences were observed between PCR-positive and negative patients. The case fatality rate for Lassa fever was 31%. Nearly two thirds of confirmed cases attended the emergency departments of ISTH. The time window for therapeutic intervention was extremely short, as 50% of the fatal cases died within 2 days of hospitalization--often before ribavirin treatment could be commenced. Fatal Lassa fever cases were older (p = 0.005), had lower body temperature (p<0.0001), and had higher creatinine (p<0.0001) and blood urea levels (p<0.0001) than survivors. Lassa fever incidence in the hospital followed a seasonal pattern with a peak between November and March. Lassa virus sequences obtained from the patients originating from Edo State formed--within lineage II--a separate clade that could be further subdivided into three clusters. CONCLUSIONS/SIGNIFICANCE: Lassa fever case management was improved at a tertiary health institution in Nigeria through establishment of a laboratory for routine diagnostics of Lassa virus. Data collected in two years of operation demonstrate that Lassa fever is a serious public health problem in Edo State and reveal new insights into the disease in hospitalized patients.